Geographic and Temporal Trends in Isolation and Antifungal Susceptibility of Candida parapsilosis : a Global Assessment from the ARTEMIS DISK Antifungal Surveillance Program, 2001 to 2005 - (:unkn) unknown (My University, 2008)
ABSTRACT We examined data from the ARTEMIS DISK Antifungal Surveillance Program to describe geographic and temporal trends in the isolation of Candida parapsilosis from clinical specimens and the in vitro susceptibilities of 9,371 isolates to fluconazole and voriconazole. We also report the in vitro susceptibility of bloodstream infection (BSI) isolates of C. parapsilosis to the echinocandins, anidulafungin, caspofungin, and micafungin. C. parapsilosis represented 6.6% of the 141,383 isolates of Candida collected from 2001 to 2005 and was most common among isolates from North America (14.3%) and Latin America (9.9%). High levels of susceptibility to both fluconazole (90.8 to 95.8%) and voriconazole (95.3 to 98.1%) were observed in all geographic regions with the exception of the Africa and Middle East region (79.3 and 85.8% susceptible to fluconazole and voriconazole, respectively). C. parapsilosis was most often isolated from blood and skin and/or soft tissue specimens and from patients hospitalized in the medical, surgical, intensive care unit (ICU) and dermatology services. Notably, isolates from the surgical ICU were the least susceptible to fluconazole (86.3%). There was no evidence of increasing azole resistance over time among C. parapsilosis isolates tested from 2001 to 2005. Of BSI isolates tested against the three echinocandins, 92, 99, and 100% were inhibited by concentrations of ≤2 μg/ml of anidulafungin (621 isolates tested), caspofungin (1,447 isolates tested), and micafungin (539 isolates tested), respectively. C. parapsilosis is a ubiquitous pathogen that remains susceptible to the azoles and echinocandins; however, both the frequency of isolation and the resistance of C. parapsilosis to fluconazole and voriconazole may vary by geographic region and clinical service.
Geographic and Temporal Trends in Isolation and Antifungal Susceptibility of Candida parapsilosis